1983
DOI: 10.1128/jb.155.3.1015-1026.1983
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome transfer and R-prime plasmid formation mediated by plasmid pULB113 (RP4::mini-Mu) in Alcaligenes eutrophus CH34 and Pseudomonas fluorescens 6.2

Abstract: Plasmid pULB113 (RP4::mini-Mu), which contains the mini-Mu transposon, promoted both homologous and heterologous gene transfer from Pseudomonas fluorescens 6.2 and Alcaligenes eutrophus CH34. Homologous gene transfer in P. fluorescens 6.2 and A. eutrophus CH34 occurred at a frequency of 10-4 to 10-5, and recombinants inherited unselected recessive markers, suggesting a process of chromosome mobilization. Loci involved in autotrophic growth were among those transferred in A. eutrophus. In heterospecific matings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Transfer of metal resistance markers to other strains supported this view [7–9]. The strain proved also to be accessible to genetic analysis and to act as a good recipient of foreign genes in plasmid‐mediated mobilization of chromosomal genes between different bacteria [10]. As a facultative chemolithotrophic bacterium able to grow aerobically in the presence of H 2 and CO 2 , strain CH34 was shown to possess two hydrogenases, one soluble and one particle‐bound, which at that time was considered typical for A. eutrophus [2].…”
Section: Introduction:ralstonia Metallidurans: General Description Amentioning
confidence: 79%
See 1 more Smart Citation
“…Transfer of metal resistance markers to other strains supported this view [7–9]. The strain proved also to be accessible to genetic analysis and to act as a good recipient of foreign genes in plasmid‐mediated mobilization of chromosomal genes between different bacteria [10]. As a facultative chemolithotrophic bacterium able to grow aerobically in the presence of H 2 and CO 2 , strain CH34 was shown to possess two hydrogenases, one soluble and one particle‐bound, which at that time was considered typical for A. eutrophus [2].…”
Section: Introduction:ralstonia Metallidurans: General Description Amentioning
confidence: 79%
“…Conjugation experiments, the isolation and characterization of R‐prime plasmids [10,65], the construction of a cosmid library [39], and the development of electroporation [66] allowed the circularity of the chromosome to be established and various loci to be mapped [10,16,65,67,68]. Genetic and physical maps of the pMOL28 plasmid and its conjugation‐proficient derivative pMOL50 were produced [14].…”
Section: Introduction:ralstonia Metallidurans: General Description Amentioning
confidence: 99%
“…The plasmicl pULB113 has been reported to transfer efficiently from E. coli to Salmonella tvphimurium, Klebsiella pneurnoniae, and Proteus rnirabilis (19) Pseudomona s fluorescens and Alcali genes eutrophus (8) , Erwinia carotozora (15) and Shigella dvsenteriae 1 (18). In this study, we have demonstrated transfer of this plasmid to enterotoxigenic E. cal, enteropathogenic E. coli, V. cholerae 01 and the other three species of Shigella.…”
Section: Discussionmentioning
confidence: 58%
“…In our study, the R-primes were recovered at a rather high frequency, 10-5 per recipient cell, which is similar to the frequency of recovery of R-prime plasmids in other species of enterobacteriaceae, such as E. coli, K. pneumoniae, Salmonella typhimurium and Proteus mirabilis (19), and Erwinia carotovora subsp. chrysanthemi (15,20) and also in other bacteria outside enterobacteriaceae (8).…”
Section: Discussionmentioning
confidence: 99%
“…To con¢rm the presence of plasmid pEMT1k in potential transconjugants formed in soil inoculated with UWC3(pEMT1k), the re-transfer of this plasmid was examined using E. coli CM330 as recipient in plate matings, performed as described previously [18]. E. coli transconjugants were selected on LB agar containing kanamycin (50 mg l 3I ), incubated at 43³C.…”
Section: Conjugation and Con¢rmation Of Plasmid Transfermentioning
confidence: 99%